The Role of Shopping Enjoyment in Mediating the Influence of Hedonic Motivation On Impulse Buying At Miniso in Denpasar - Dayananda Sarasvati Mas Putri; I Gst. A. Kt. Gd. Suasana (International Journal of Management Research and Economics, 2024)
The development of various business activities is increasing, one example of business development that causes positive changes is the retail business. Retail is an example of a type of business activity that has rapid development in Indonesia. With this potential, business opportunities are formed in the retail sector. This research was conducted at Miniso in Denpasar. The purpose of this study was to test and explain the role of shopping enjoyment in mediating hedonic motivation on impulse buying at Miniso in Denpasar. There was 120 respondents in this study sample. Data collection was carried out by distributing questionnaires via google form. The classical assumption test, path analysis test, sobel test, and VAF test were used to analyze the gathered data. The results of this study state that hedonic motivation has a significant positive effect on impulse buying, hedonic motivation has a significant positive effect on shopping enjoyment, shopping enjoyment has a significant positive effect on impulse buying, and shopping enjoyment can partially mediate the influence of hedonic motivation on impulse buying at Miniso in Denpasar. By taking consider to the elements of hedonic motivation and shopping enjoyment, Miniso can use the implications of this study as input and consideration in order to preserve consumers.